Search for first generation leptoquark pair production in the electron plus missing energy plus jets final state - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Aoki, M.; Vertogradov, L. S.; et al. (Amer Physical Soc, 2011)
We present a search for the pair production of first generation scalar leptoquarks (LQ) in data corresponding to an integrated luminosity of 5.4 fb(-1) collected with the D0 detector at the Fermilab Tevatron Collider in p (p) over bar collisions at root s = 1.96 TeV. In the channel LQLQ -> eqv(e)q', where q, q' are u or d quarks, no significant excess of data over background is observed, and we set a 95% C. L. lower limit of 326 GeV on the LQ mass, assuming equal probabilities of LQ decays to eq and v(e)q'.